Pengaruh Disiplin Kerja, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT Sebastian Jaya Metal: The Effect of Work Discipline, Work Motivation, and Job Satisfaction on Employee Performance at PT Sebastian Jaya Metal - Chaidar Yuki kazuwari; Faif Yusuf (CV Warnak Johanna Nusantara, 2025)
This study aims to examine the Influence of Work Discipline, Work Motivation, and Job Satisfaction on Employee Performance at PT. Sebastian Jaya Metal. The research method used is a survey with a quantitative approach, involving all employees of PT. Sebastian Jaya Metal totaling 80 people. Data were collected through a questionnaire adapted from a scale that has been tested for validity and reliability. The results of this study used several testing methods, namely, Data Quality Test, Classical Assumption Test, Hypothesis Test, and Determination Coefficient Test. The tool used to process data in this study is SPSS software version 26. Based on the test results, it is shown that the significance is 0.000 <0.05 and the f count value is 202.628 which is greater than the f table with a value of 3.12, it can be concluded that the variables Work Discipline, Work Motivation, and Job Satisfaction together (simultaneously) have a significant effect on the Employee Performance variable at PT. Sebastian Jaya Metal. Then the results of the t-test show that the variable Work discipline has a significant effect on the performance of PT. Sebastian Jaya Metal employees, the variable work motivation has a significant effect on the performance of PT. Sebastian Jaya Metal employees, and job satisfaction also has a significant effect on the performance of PT. Sebastian Jaya Metal employees.